Research progress of fecal microbiota transplantation in the treatment of radiation enteritis - Cui Jiaqu; Chen Qiyi; Li Ning (结直肠肛门外科)
Radiotherapy, as an important component of the comprehensive treatment of malignant tumors, helps to improve the prognosis of cancer patients. However, radiation can cause damage to healthy tissues and induce corresponding adverse reactions. In the treatment of abdominal and pelvic malignancies, the healthy intestines are inevitably included in the radiation field. The damage to normal intestinal epithelial cells leads to intestinal mucositis, namely radiation enteritis. Radiation enteritis affects the intestinal microbiota and severely impacts the quality of life and prognosis of patients. Currently, there is no effective clinical treatment for radiation enteritis. This article aims to explore the correlation between radiation enteritis and the intestinal microbiota, as well as the research progress of fecal microbiota transplantation in the treatment of radiation enteritis.